Association of hippocampal calcification and cardiovascular risk factors in two patient cohorts. (2019) - van der Knaap, Marije J.A.; Peters, Melissa E.M.; Lucci, Carlo; Geerlings, Mirjam I.; de Jong, Pim A.; Ruigrok, Ynte M.; ,; Algra, A.; van der Graaf, Y.; Grobbee, D.E.; Rutten, G.E.H.M.; Visseren, F.L.J.; et al.
Abstract: Background and aims: Hippocampal calcification is a recently described type of intracranial calcification and might be a risk factor for ischemic stroke and dementia. Data on its risk factors and insight into the etiology are limited. We aimed to investigate the association of risk factors for hippocampal calcification in two independent cohorts in the Netherlands. Methods: Unenhanced CT scans of the brain were scored for the presence and severity of hippocampal calcification in two independent prospectively collected patient cohorts, the first consisting of aneurysmal subarachnoid hemorrhage (SAH) patients (N = 741) and the second of patients participating in the Second Manifestation of ARTerial disease (SMART) study (N = 498). We estimated the association of the risk factors age, sex, smoking, dyslipidemia, overweight, hypertension, diabetes, family history, cardiac history, cerebrovascular history, use of vitamin K antagonists and renal disease with the presence and moderate/severe calcification using logistic regression analysis. Results: In both cohorts, age ≥60 years was associated with the presence of hippocampal calcification (odds ratio (OR) 2.47, 95% confidence interval (CI) 1.37–4.45 in SAH and OR 1.91, 95% CI 1.30–2.82 in SMART); in SMART, age was associated with moderate/severe calcification as well (OR 2.77, 96%CI 2.77 (1.36–3.65). All other risk factors, including a cumulative risk score of 5 or more risk factors, did not show any association with hippocampal calcification presence or severity. Conclusions: We identified age as a risk factor for hippocampal calcification. All other risk factors studied were not associated with hippocampal calcification. This contradicts findings on arterial calcifications elsewhere in the body. Therefore, more research is needed to understand this discrepancy. Graphical abstract: Image 1 Highlights: Older age is a risk factor for presence and severity of hippocampal calcification Other cardiovascular risk factors are not associated with hippocampal calcification A cumulative risk score was not associated with hippocampal calcification These results are new and unexpected compared to other calcification locations